2006
DOI: 10.1111/j.1600-0420.2006.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel clinical application of sterilized, freeze‐dried amniotic membrane to treat patients with pterygium

Abstract: ABSTRACT.Purpose: To evaluate the use of sterilized, freeze-dried amniotic membrane (FD-AM) transplantation for pterygium surgery. Methods: This study involved a prospective, non-comparative, interventional case series. Thirteen eyes of 13 patients with primary (eight eyes) or recurrent (five eyes) pterygium were studied. After excision of the pterygium fibrous tissues and application of intraoperative use of mitomycin-C, sterilized FD-AM was sutured over the bare scleral defect. The integrity of the FD-AM gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
1
40
1
2
Order By: Relevance
“…In fact, the biological characterization of sterilized, freeze-dried AM used in ocular surface reconstruction and its effectiveness has been already reported (Nakamura et al 2004;Nakamura et al 2006;Sekiyama et al 2007). This is the first work focused on the biological content of freeze-dried, powdered and sterilized hAM specifically prepared for topical use; any clinical trials on its possible in vivo effectiveness have been already reported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, the biological characterization of sterilized, freeze-dried AM used in ocular surface reconstruction and its effectiveness has been already reported (Nakamura et al 2004;Nakamura et al 2006;Sekiyama et al 2007). This is the first work focused on the biological content of freeze-dried, powdered and sterilized hAM specifically prepared for topical use; any clinical trials on its possible in vivo effectiveness have been already reported.…”
Section: Discussionmentioning
confidence: 96%
“…These papers reported the effectiveness of sterilized, freeze-dried hAM used for ocular surface reconstruction, investigating effects of preservative processes on the in vitro and in vivo (Nakamura et al 2004;Nakamura et al 2006;Sekiyama et al 2007) properties of hAM.…”
Section: Introductionmentioning
confidence: 99%
“…AM is now commonly used as a permanent graft or a temporary patch in a plethora of conjunctival and corneal procedures [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that the characteristics of AM are preserved by lyophilization (15) and the use of this tissue gives good results in ocular surface reconstruction after pterygium surgery (16) . This method reduces preservation costs, facilitates storage and transport, and may encourage the use of AM in surgical procedures.…”
Section: Abstract Introductionmentioning
confidence: 99%